Intelligent virtual agents : 15th International Conference, IVA 2015, Delft, the Netherlands, August 26-28, 2015 : proceedings /: 15th International Conference, IVA 2015, Delft, the Netherlands, August 26-28, 2015 : proceedings. ([2015]) - Unknown
No abstract available